Cortical Visual Impairment in CDKL5 Deficiency Disorder - Quintiliani, Michela; Ricci, Daniela; Petrianni, Maria; Leone, Simona; Orazi, Lorenzo; Amore, Filippo; Gambardella, Maria Luigia; Contaldo, Ilaria; Veredice, Chiara; Perulli, Marco; Musto, Elisa; Mercuri, Eugenio Maria; et al. (Frontiers in Neurology, 2022)
Background CDKL5 deficiency disorder (CDD) is a developmental encephalopathy caused by pathogenic variants in the gene cyclin-dependent kinase-like 5. Cerebral visual impairment (CVI) is frequent in patients with CDD. In addition to being recognized as a specific feature of the pathology, it has been suggested that visual impairment may correlate with neurodevelopmental outcome and epilepsy severity, but no systematic behavioral visual assessment has been performed. The aim of our study was to evaluate clinical and electrophysiological profile of CVI in patients with CDD, to correlate various aspects of visual function to neurodevelopmental and epileptic features. Methods The study included all patients with CDD from the National Pathology Registry. All patients underwent neurological examination, a disease-specific functional assessment, structured clinical evaluation of visual functions, including pattern reversal visual evoked potential (VEP), and a detailed monitoring of epileptic features, including video-EEG. Results All the 11 patients recorded in the CDKL5 national registry, 10 females and one male, age range of 1.5 to 24 years (mean 9, SD 7.7, median 6.5), were enrolled. Visual function is impaired in all patients; in particular, visual fields, visual acuity, contrast sensitivity, and stereopsis were consistently abnormal whereas other aspects, such as fixing and tracking, were relatively preserved. Pattern reversal VEP was abnormal in nearly 80% of our patients. No correlation was found among CVI severity, age, level of psychomotor development, EEG abnormalities, and pathology stages even if an overall less abnormal EEG pattern was more often associated with better visual results. Conclusion In conclusion, CVI can be considered as a major feature of CDD with a diffuse involvement in several behavioral and electrophysiological aspects. Larger cohorts will help to better clarify the possible prognostic role of EEG severity in predicting both visual and developmental abnormalities.